One-stage surgery by a combined anterior-posterior approach to treat ankylosing spondylitis complicated by a multiple-level cervical vertebral chance fracture. Issue 2 (March 2015) - Xiang, Liang-Bi; Yu, Hai-Long; Liu, Jun; Chen, Yu; Yang, Hui-Feng
Abstract Objectives. This study aimed to investigate the outcomes after using a combination of anterior–posterior approaches to treat ankylosing spondylitis (AS) complicated by a multiple-level cervical vertebral Chance fracture. Methods. We retrospectively analyzed 11 patients with AS complicated by a multiple-level cervical vertebral Chance fracture. Results. After surgery, the average follow-up period was 25 months (24–27 months). No injury to the spinal cord, nerve roots, or vessels was caused by screw insertion during the operation. The incisions for all the patients healed by primary intention. These fractures generally required 4–6 months (average, 4.5 months) to heal, and there was no loosening, pullout or collapse of the bone graft, loosening or breaking of the internal fixators, nonunion, or other complications. Conclusions. Therefore, management with a combination of anterior–posterior approaches is feasible for treating AS complicated by a multiple-level cervical vertebral Chance fractures.